2014
DOI: 10.1063/1.4863077
|View full text |Cite
|
Sign up to set email alerts
|

Ordering recombinant silk-elastin-like nanofibers on the microscale

Abstract: Self-assembled peptide/polypeptide nanofibers are appealing building blocks for creating complex three-dimensional structures. However, ordering assembled peptide/polypeptide nanofibers into three-dimensional structures on the microscale remains challenging and often requires the employment of top-down approaches. We report that silk-elastin-like protein polymers selfassemble into nanofibers in physiologically relevant conditions, the assembled nanofibers further form fiber clusters on the microscale, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Zeng et al. showed that microscale porous hydrogels are derived from interconnected clusters of polymer nanofibers ( Figure ) . The stimuli‐responsive behavior of SELPs and the diversity of structures they form, combined with post‐processing techniques such as electrospinning or thin film deposition, have made them useful for various applications in drug delivery (chemoembolics, in situ enemas, and adenovirus delivery) as well as in tissue engineering, and wound healing …”
Section: Using Protein Order and Disorder In Hierarchical Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Zeng et al. showed that microscale porous hydrogels are derived from interconnected clusters of polymer nanofibers ( Figure ) . The stimuli‐responsive behavior of SELPs and the diversity of structures they form, combined with post‐processing techniques such as electrospinning or thin film deposition, have made them useful for various applications in drug delivery (chemoembolics, in situ enemas, and adenovirus delivery) as well as in tissue engineering, and wound healing …”
Section: Using Protein Order and Disorder In Hierarchical Assemblymentioning
confidence: 99%
“…Temperature‐triggered phase separation of these POPs yields porous, physically crosslinked, viscoelastic networks. (a) Reproduced with permission . Copyright 2014, AIP Publishing.…”
Section: Using Protein Order and Disorder In Hierarchical Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…combined β ‐sheet forming GAGAGS motifs with ELPs to form silk‐elastin‐like protein (SELP) polymers which self‐assemble into nanofibers at 37 °C which further coalesce into microscale clusters leading to the formation of macroscopically continuous structures with distinct nanoscale and microscale architectures. [ 203 ] Mozhdehi et al. generated genetically encoded lipid‐polypeptide hybrid biopolymers called fatty acid modified ELPs (FAMEs).…”
Section: Applications For Idpps With Nanoscale and Microscale Control Enabled By Llpsmentioning
confidence: 99%
“…Concentration is an extra parameter that governs the growth of SELR nanofibers. Thus, the micelle-like nanoparticles that arise during the early stages of self-assembly act by increasing the polypeptide density, thus prompting close approach of the silk-like domains, which subsequently self-assemble into nanofibers (Zeng et al, 2014b). Upon reaching this state, the soluble SELR begin to add, via diffusion pathways, to the formed structures, which evolve into different arrangements depending on the concentration.…”
Section: Silk-elastin-like Recombinamers (Selrs) and Silk-tropoelastin Biomaterialsmentioning
confidence: 99%